KAJIAN HUKUM PENGHENTIAN TERAPI BANTUAN HIDUP (WITHDRAWING OF LIFE SUPPORT) DALAM PERAWATAN PALIATIF - sediatmojo, agung sediatmojo (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2021)
Abstract— Withdrawing of life support was chosen as a preventive measure for the suffering of a person with an incurable disease. This action was taken because there is no other way that can help a person to escape the terrible suffering at the end of his life. Withdrawing of life support should observe the principle of Palliative Care, it does not aim to accelerate or prolong the patient's life. This research analyzes the legal norms of Withdrawing of life support using a statute approach, a conceptual approach and a comparative approach. The aim is to examine whether this action can be classified as an illegal act and what is the legal responsibility for the doctor who did it. Withdrawing of life support as Palliative Care is still continuing the normal treatment as a form of maintaining the quality of life for patients, while extraordinary treatments that are felt to be useless and futile. Determining what is ordinary or extraordinary is very important so that doctors and nurses can be sure that their professional actions do not violate ethics or law. Doctors as perpetrators of withdrawing of life support in Indonesia cannot be classified as a criminal crime against life. In outward acts (actus reus), these actions can result in the loss of a person's life. But the mental attitude (mens rea) to Withdrawing of Life Support is very different from murder. Civil liability arises when there is a violation of the rights of others, a violation of the perpetrator's legal obligations, violates decency and morality and violates the behavior of a good citizen. Good citizen behavior for a doctor refers to professional standards, standard operating procedures, medical code of ethics and the behavior of other colleagues.Keyword: legal aspect; responsibility; withdrawing of life support; palliative care